2013
DOI: 10.1037/a0034209
|View full text |Cite
|
Sign up to set email alerts
|

Is skills training necessary for the primary prevention of marital distress and dissolution? A 3-year experimental study of three interventions.

Abstract: These findings highlight the potential value of cost-effective interventions such as RA, cast doubt on the unique benefits of skill-based interventions for primary prevention of relationship dysfunction, and raise the possibility that skill-based interventions may inadvertently sensitize couples to skill deficits in their relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(149 citation statements)
references
References 30 publications
8
135
3
3
Order By: Relevance
“…More specifically, the analyses presented in Table 4 were consistent with recent treatment findings (e.g., Rogge et al, 2013) suggesting that unidimensional measures of global sentiment can potentially obscure meaningful treatment results revealed by bi-dimensional measures like the QSI. Thus, although researchers could choose to include a single subscale of the QSI in their studies, we would recommend that they include both sexual satisfaction and dissatisfaction as distinct outcomes in their studies, modeling them separately so as to gain a more comprehensive understanding of couples' sexual quality.…”
Section: Distinguishing Dissatisfaction From Satisfactionsupporting
confidence: 83%
See 2 more Smart Citations
“…More specifically, the analyses presented in Table 4 were consistent with recent treatment findings (e.g., Rogge et al, 2013) suggesting that unidimensional measures of global sentiment can potentially obscure meaningful treatment results revealed by bi-dimensional measures like the QSI. Thus, although researchers could choose to include a single subscale of the QSI in their studies, we would recommend that they include both sexual satisfaction and dissatisfaction as distinct outcomes in their studies, modeling them separately so as to gain a more comprehensive understanding of couples' sexual quality.…”
Section: Distinguishing Dissatisfaction From Satisfactionsupporting
confidence: 83%
“…In fact, these results began to suggest that collapsing positive and negative evaluations into a single dimension (asiscurrentpracticewiththeexistingscales)mightobscuremeaningful longitudinal results. Consistent with this, a recent study examining relationship enhancing interventions in a sample of 174 couples followed over the first 3 years of marriage demonstrated significant outcome differences across intervention groups for positive but not negative relationship evaluations, and those differences were obscured when a unidimensional scale was used to model relationship quality (Rogge et al, 2013). The current results suggested that the use of unidimensional scales like the ISS, YSSS, or PSSI could potentially be obscuring results in a similar manner.…”
Section: Distinction Between Satisfaction and Dissatisfactionsupporting
confidence: 81%
See 1 more Smart Citation
“…We argue that eliminating stress at its source may hold unique advantages, in part because direct efforts to intervene with couples might heighten awareness of relationship weaknesses [15]. Efforts to reduce stress with interventions that operate 'below the radar' -that is, largely outside of couple awareness --can promote relationship well-being while incurring fewer costs for the couples themselves.…”
Section: Protecting Relationships By Eliminating Stressmentioning
confidence: 99%
“…In the absence of a no intervention control it is not possible to conclude that the controlled reading program had a positive effect. However, Rogge, Cobb, Lawrence, Johnson, and Bradbury (2013) found that couples who watched and discussed movies about intimate relationships reaped similar benefits to couples receiving skill-based RE. There is considerable debate in the literature around whether active skills training such as that included in…”
Section: Resultsmentioning
confidence: 99%